Diagnostic work up of patients with increased bleeding tendency. Issue 2 (30th December 2019) - Zegers, Suzanne A. M.; Smit, Yolba; Saes, Joline L.; van Duren, Clint; Schuijt, Tim J.; van Heerde, Waander L.; Schols, Saskia E. M.
Abstract: Introduction: The diagnostic trajectory of patients with increased bleeding tendency can be very costly and time‐consuming. In addition, previous studies have shown that half of these patients remain without final diagnosis despite all efforts. Aim: This study aimed to improve insight into the current diagnostic process of these patients. Methods: A total of 117 adult patients, referred to an academic hospital because of being suspected to have an increased bleeding tendency, were included. Different parameters were compared between patients receiving final diagnosis, patients without final diagnosis but a high Tosetto bleeding assessment tool (BAT) score (classified as bleeding of unknown cause, or BUC) and a control group consisting of patients without final diagnosis and a low BAT score. Results: The BAT score was significantly higher in patients in the BUC group as compared to patients reaching final diagnosis (8.1 vs 4.9). Interestingly, the two subcategories most prevalently increased were surgery and post‐partum haemorrhage‐associated bleeding (surgery: 2.1 vs 1.1; post‐partum haemorrhage: 0.7 vs 0.0). Laboratory screening results were more often abnormal in patients reaching final diagnosis compared to patients remaining without diagnosis and a high BAT score (n = 32 (78%) vs n = 14 (46%), 95% CI 1.5‐12), especially concerning the PFA (=27 (66%) vs n = 10 (33%), 95% CI 1.4‐10) and von Willebrand factor activity levels (n = 11 (27%) vs n = 1 (3%), 95% CI 1.3‐91). Conclusion: Isolated high bleeding score on surgical or post‐partum bleeding correlates with a lower chance of receiving final diagnosis. Withholding extensive haemostatic testing should be considered. Better screening and confirmative haemostatic assays are still needed.